Factors influencing crossability among triticale and wheat and its subsequent effect along with hybrid necrosis on haploid induction. (2nd April 2016) - Jamwal, Navdeep S.; Chaudhary, H. K.; Badiyal, Anila; Hussain, Waseem
ABSTRACT: Gene introgression in wheat is not only limited by crossability but also affected by environmental conditions, genotypic differences and necrotic genes. Hence, the present investigation was formulated to determine the influence of genotypic and environmental factors on the crossability of elite triticale and wheat genotypes, screen the effect of necrotic genes in the F1 hybrids and the relative performance of hybrids towards haploid induction following the Imperata cylindrica -mediated chromosome elimination approach. The dry temperate region was observed to be significantly better than sub-humid mid-hills for seed set in intergeneric crosses. Lower rate of crossability (17.49–48.33% and 14.46–36.51%) was found in triticale × wheat crosses at both locations. The hybrids having HPW236 as one of the parent revealed necrosis ranging from the lowest to highest grade. Further, negative influence of the necrotic genes on the haploid induction parameters was apparent due to significant hybrid necrosis symptoms in F1 hybrids. Statistically significant variation in haploid induction parameters was also evident between and within different cross combinations, indicating that haploid induction parameters were profoundly influenced by genotypic specificity.